Correction for Vol.10(2): 1-8 (Dec. 2012) (The Agriculturists, 2013)
ErratumIn the paper entitled Marker-assisted Foreground Selection for Identification of Salt Tolerant Rice Genotypes published in The Agriculturists 10(2): 1-8 (December 2012), the authors should be read as M. S. Alam, S. N. Begum, M. M. Islam, M. Moniruzzaman and M. A. K. Patwary instead of M. S. Alam, M. Salim, M. Moniruzzaman, J. A. Rashid and M. M. Islam.DOI: http://dx.doi.org/10.3329/agric.v11i1.15289 The Agriculturists 2013; 11(1)